Efficacy of Bariatric Surgery in Type 2 Diabetes Mellitus Remission: the Role of Mini Gastric Bypass/One Anastomosis Gastric Bypass and Sleeve Gastrectomy at 1 Year of Follow-up. A European survey - Musella, M (2016)
BACKGROUND: A retrospective study was undertaken to define the efficacy of both mini gastric bypass or one anastomosis gastric bypass (MGB/OAGB) and sleeve gastrectomy (SG) in type 2 diabetes mellitus (T2DM) remission in morbidly obese patients (pts). METHODS: Eight European centers were involved in this survey. T2DM was preoperatively diagnosed in 313/3252 pts (9.62%). In 175/313 patients, 55.9% underwent MGB/OAGB, while in 138/313 patients, 44.1% received SG between January 2006 and December 2014. RESULTS: Two hundred six out of 313 (63.7 %) pts reached 1 year of follow-up. The mean body mass index (BMI) for MGB/OAGB pts was 33.1 ± 6.6, and the mean BMI for SG pts was 35.9 ± 5.9 (p < 0.001). Eighty-two out of 96 (85.4%) MGB/OAGB pts vs. 67/110 (60.9%) SG pts are in remission (p < 0.001). No correlation was found in the % change vs. baseline values for hemoglobin A1c (HbA1c) and fasting plasma glucose (FPG) in relation to BMI reduction, for both MGB/OAGB or SG (ΔFPG 0.7 and ΔHbA1c 0.4 for MGB/OAGB; ΔFPG 0.7 and ΔHbA1c 0.1 for SG). At multivariate analysis, high baseline HbA1c [odds ratio (OR) = 0.623, 95% confidence interval (CI) 0.419-0.925, p = 0.01], preoperative consumption of insulin or oral antidiabetic agents (OR = 0.256, 95% CI 0.137-0.478, p = <0.001), and T2DM duration >10 years (OR = 0.752, 95% CI 0.512-0.976, p = 0.01) were negative predictors whereas MGB/OAGB resulted as a positive predictor (OR = 3.888, 95% CI 1.654-9.143, p = 0.002) of diabetes remission. CONCLUSIONS: A significant BMI decrease and T2DM remission unrelated from weight loss were recorded for both procedures if compared to baseline values. At univariate and multivariate analyses, MGB/OAGB seems to outperform significantly SG. Four independent variables able to influence T2DM remission at 12 months have been identified.